Econometric Analysis of Tobacco Production in Syria during the Period 1990-2017 - يعقوب غسان; العشعوش أيمن; نعامه مجد (Latakia University Journal -Biological Sciences Series, 2020)
The research aimed to study the reality of tobacco cultivation and development at the level of the Syrian Arab Republic during the period 1990-2017, and to estimate the general trend equation to represent the relationship between production and the factors affecting it during the aforementioned period. This research relied mainly on the secondary data of the World Food and Agriculture Organization (FAO) during the study period, and on the inductive method of analysis in both descriptive and quantitative terms, using the linear analysis of the regression models in their various mathematical forms, as well as followed econometric methods, such as indices and equations The general trend and analysis of variance, as a function (Cobb-Douglas) was elected to represent the relationship between production, productivity and cultivated area during the studied period. The research results showed that the production of the tobacco crop reached a maximum in 2005 about 28870 tons, with a record number of 220.38%, an increase of 120.38% over 1990. As for the cultivated area, its maximum reached in 2000 about 8100 hectares. With a record number of 141.40%, an increase of 41.40% over the year 1990. The results of the research also showed that the best standard model for estimating general trend equations for area development, production and productivity of tobacco yield at the level of the Syrian Arab Republic during the period under consideration is the cubic model. The production function (Cobb-Douglas) showed a direct relationship between the production variable as a dependent variable and variables ( Time, area, productivity) as independent variables. This research reached a set of recommendations, the most important of which is the necessity of using econometric models in studying the development of agricultural production and taking agricultural economic decisions, due to its distinctive estimation, simulation of reality and forecasting future values.